The invasion of Panama through post-conflict literature : collective memory in mimetic and thematic characterization - Limnio Grimaldo, Kaaubi Alfonso
To conceptualize literature it is a complex task. If one were to define the term to its upmost simple degree, it would be along the unes of a written form of art, but to formulate it just as that it subtracts ah cultural and historical configurations, since literature comprises a rich legacy that explores the nuances of the human condition. Part of that condition is the ability to examine the past and make sense of it. Consequently, this thesis seeks to answer how literature aimed at the invasion can help Panamanian collective to produce, understand, and reimagine memories of the event. The invasion perpetuated by the United States of America in 1989, under the so-called "Just Cause Operation", represented a conflict with catastrophic consequences that are still rippling to this day. Although research, reports, articles, and books have been written about the effects in economics, history, and politics; little has been done to analyze how this conflict prompted a countercultural artistic movement. Documentaries, movies, music, museum exhibitions, and hiterary works in genres such as poetry, fiction, and others have been employed to express and discuss the collective anger, grief, and trauma caused by the invasion. Nevertheless, the ideological clashes pushed forward by the lack of interest of this matter in school curriculums, governments, and interest groups have turned out to be a state of collective amnesia in the Panamanian society-a state in which the time to look retrospectively into history seemed to have been replaced by the mainstream, spectacular, and temporary fulfillment.